Coupling gas flow pattern and kinetics for tyre pyrolysis modelling. (29th June 2019) - Arabiourrutia, M.; Lopez, G.; Aguado, R.; Bilbao, J.; Olazar, M.
Highlights: The residence time distribution of the gas in the pyrolysis plant was studied. The E curves have been determined for the pyrolysis plant. Two models have been proposed to simulate the gas flow pattern. The flow model has been coupled with the kinetic one to study pyrolysis kinetics. Abstract: A novel strategy has been proposed for the rigorous kinetic modeling of tyre pyrolysis in a conical spouted bed reactor. A kinetic model coupled with a gas flow model was used in the fitting of experimental results obtained in a bench scale unit in the 425–610 °C range. A gas flow model should be incorporated to account for the delay and mixing phenomena observed in tracer experiments, as these phenomena cause remarkable deviations in the assessment of the kinetic parameters. The gas flow pattern from the reactor to the measuring device was modeled using two different approaches based on ideal flow reactors. Furthermore, two kinetic schemes considering lumped products have been proposed; the first one is based on four parallel independent reactions accounting for the volatile products (gas, liquid, aromatics and tar). The second one considers an additional secondary reaction of aromatic formation from the liquid. The strategy proposed for coupling the kinetics and the flow model led to a suitable fitting of the experimental results, with the performance of the model considering a secondary reaction being slightly better than the simple one.